Good governance and fiscal capacity in regional expansion: A holistic analysis of qualitative perspective - Syarifuddin Syarifuddin; Ratna Ayu Damayanti (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study aims to analyze the problem in a holistic manner of good governance and fiscal capacities in territorial splits. This study is qualitative in which the researchers made a description of the phenomenon, as well as researching the words, a detailed report of the views of informants, and conducting analysis based on the natural set-ting. The study found that the territorial splits undertaken in the Province of West Sulawesi provides the government an opportunity to integrate the three pillars of good governance. These three pillars work together in planning and implementation of regional policy. The study concludes that the territorial splits in the Province of West Sulawesi are a policy that is responsible and important from the aspect of good gover-nance. On the other hand, the study shows that the territorial splits have led to weak local fiscal capacity. This is due to the territorial splits in the area of West Sulawesi province that has not been able to encourage the growth of local fiscal capacity, which in fact it is expected to encourage the degree of fiscal autonomy of the regions.